Complex sleep apnea syndrome in a child with Chiari malformation type 1 - Yosunkaya, Sebnem; Pekcan, Sevgi (The Turkish Journal of Pediatrics, 2013)
There are few reports of a patient presenting with symptoms of obstructive sleep apnea syndrome (OSAS) as the sole manifestation of Chiari malformation type 1 (CM1). In the literature, complex sleep apnea syndrome (CompSAS) was also reported as a rare condition related to CM1 patients. We report the case of a 13-year-old patient with the complaint of snoring and difficulty in breathing during sleep, but otherwise healthy. After an initial polysomnography, the patient was diagnosed with OSAS and nocturnal continuous hypoxemia. The child underwent titration to pressure of continuous positive airway pressure (CPAP); obstructive apnea improved but central apnea (i.e., CompSAS) and nocturnal continuous hypoxemia persisted. Magnetic resonance imaging led to diagnosis of CM1. Her central apnea and nocturnal hypoxemia resolved following bi-level positive airway pressure-spontaneous-timed (S/T) (BiPAPS/ T) treatment. We emphasize that the CM1 cases can admit with only breathing problems during sleep without concomitant neurological findings, and this malformation can cause central apnea resistant to CPAP.